2009
DOI: 10.3945/ajcn.2008.26661
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption and n–3 polyunsaturated fatty acids in healthy men and women from 3 European populations

Abstract: Alcohol intake was associated with higher plasma and red blood cell concentrations of marine n-3 FAs. Components of wine other than alcohol (polyphenols) might exert these effects. Part of the alcohol-induced cardioprotection may be mediated through increased marine n-3 FAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(63 citation statements)
references
References 33 publications
5
55
1
2
Order By: Relevance
“…An intriguing fi nding of our study is the positive association between alcohol intake and plasma EPA but not DHA. A similar fi nding was observed in other studies among men ( 40,41 ), while among women both plasma EPA and DHA were associated with alcohol intake, especially wine ( 41 ). Contrarily to in vitro studies, in vivo isotope tracer studies in primates showed that moderate alcohol consumption might increase the biosynthesis of EPA and DHA from their precursor ALA, suggesting an activation of the desaturation-elongation pathway ( 42 ).…”
Section: Discussionsupporting
confidence: 68%
“…An intriguing fi nding of our study is the positive association between alcohol intake and plasma EPA but not DHA. A similar fi nding was observed in other studies among men ( 40,41 ), while among women both plasma EPA and DHA were associated with alcohol intake, especially wine ( 41 ). Contrarily to in vitro studies, in vivo isotope tracer studies in primates showed that moderate alcohol consumption might increase the biosynthesis of EPA and DHA from their precursor ALA, suggesting an activation of the desaturation-elongation pathway ( 42 ).…”
Section: Discussionsupporting
confidence: 68%
“…43 The Lyon Diet Heart Study 44 showed that moderate wine consumption in CHD patients was associated with higher . 45 The possibility that moderate consumption of alcohol raises 3 polyunsaturated fatty acid levels is of interest in the setting of secondary prevention, in which protection against CVD after AMI was found after supplementation with 3 polyunsaturated fatty acids. 46 Genetic regulation of individual response to alcohol was proposed on the basis of the relations between alcohol dehydrogenase type 3 polymorphisms, the level of alcohol consumption, and the risk of AMI.…”
Section: Costanzo Et Al Alcohol and Mortality In Cvd Patientsmentioning
confidence: 99%
“…The stimulating INTERHEART publication should motivate further scientific elaboration of the preferential harm of alcohol in South Asia and revive research targeting alcohol quality. Promising research foci may address unexplored areas, like the influence of alcohol on the gut microbiota and metabolome and the effects of distinct alcoholic beverages on lipid composition 15 and de novo lipogenesis.…”
Section: The South Asian Paradoxmentioning
confidence: 99%